Prevalence of mistreatment in veterinary medical education; a survey of 3rd year veterinary students at a single university - Katherine H. Barnes; Stephanie Johnson; Chin-Chi Liu; Karanvir S. Aulakh (BMC Medical Education, 2025)
Abstract Background Improving quality of life in veterinary medicine has emerged as an important topic. One factor which may influence quality of life in medical education is mistreatment (verbal abuse, power abuse, and physical abuse to establish and maintain a power hierarchy). Although it has been documented in medical education, its occurrence in veterinary education is not yet known. Methods Third year veterinary students were invited to participate in an anonymous and voluntary survey on mistreatment during the preclinical and clinical education. Students were asked if they witnessed and/or experienced a mistreatment, the type of mistreatment, and the person responsible for administering the mistreatment. Quality of life scores were obtained using the Medical Outcomes Trust short form questionnaire (SF-36). An analysis of variance (ANOVA) model followed by pairwise Least Significant Difference post hoc comparison was used to investigate the relationship variables. Results Fifty-five of 60 students (91.7%) that completed the questions on mistreatment indicated that they experienced and/or witnessed a mistreatment during veterinary education. 92% of students that experienced a mistreatment said that it interfered with the learning environment but only 29% of students reported the mistreatment at the time that it occurred. The most common mistreatment was public humiliation (78.3%) followed by special treatment based on gender (63.3%) and racially or ethnically offensive remarks (28.3%). Only racially or ethnically insensitive remarks were associated with a lower quality of life score in the social functioning category (p = 0.0131). Conclusions Mistreatment frequently occurred during the preclinical and clinical education of veterinary students in this population and interfered with the learning environment. The only mistreatment associated with a lower quality of life score was racially insensitive remarks. Programs to educate students and clinicians/staff about mistreatment and how to handle education in a stressful clinical and a preclinical setting may be of benefit in the future. Clinical trial number Not applicable.